Occurrence of Amoebic Versus Bacillary Dysentery among Children Under Five Years of Age in Baghdad City - Zaidan, Ali Awad; Al Jiboory, Riyadh KL (AL-Kindy College Medical Journal, 2013)
Background: During Annual statistical report published by the Iraqi ministry of health the year 2004 showed that mortality rate was 0.15 per 1000 of diarrheal episodes among children under five years.Objectives: To study the occurrence of Shigellosis and Entamoeba histolytica in a sample of children from certain hospitals in Baghdad and determine its relation to some demographic factors.Methods: This cross sectional study was carried out in Baghdad city involving 400 children with bloody diarrhea under five years of age attending four hospitals, 130 cases from Central Pediatric Hospital, 110 cases from Al Mansoor Pediatric Hospital, 90 cases from Al Kadhimya Teaching Hospital and 70 cases from Mohammed Baaqir Al Hakeem Hospital for the period from the first of January through October 2005. Stool specimens were examined microscopically for detection the amoebic dysentery and negative cases were sent for stool culture for detection of Shigellosis. Results: The study revealed that Entamoeba histolytica was the most frequently identified cause of bloody diarrhea 362 (90.5%), while shigella was identified in 38 cases (9.5%). young children below two years of age were more liable to have diarrhea than other age group. Both shigella and amoebic cases shared the following risk factors, lack of breast feeding, unboiled water, low level of education of mother and overcrowding.Conclusions: Child health services should concentrate on health education of mother to encourage breast feeding, boiling of water, general personal and environmental hygiene to prevent spread of these infection.